Genetic variation of CYP3A and its influence on the pharmacokinetics of tacrolimus, a calcineurin inhibitor - Gupta, Ajay Kumar; Ramashankar, M. M.; Kumar, Mahadevan (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Tacrolimus (Tac) a calcineurin inhibitor (CNI), is a potent immunosuppressive drug which is widely used in organ transplant recipients. The drug has a narrow therapeutic window and high inter-individual pharmacokinetic variability. Tac is metabolized by cytochrome P450 3A (CYP3A) enzymes. The CYP3A5 activity is largely determined by the single nucleotide variant (SNV) CYP3A5*3 (c.219-237A>G; rs776746), which results in alternate mRNA splicing and a non-functional protein. Methods: An observational prospective study was carried out at nephrology centre of army hospital where the consenting patients were enrolled in the study. The whole blood sample drawn was utilized to analyze for plasma drug concentration of Tac and genotyping for the CYP3A*5 polymorphism by the method as described by Cheung et al. Results: 100 patients participated with an average of 98±8 days after transplantation. Recipients having heterozygous CYP3A5*1 genotype manifested 70% lower mean steady state concentration of Tac (C0/D ratio) 1.67±0.43 μg*l-1/mg in comparison to homozygote carriers of CYP3A5*3 5.60±1.94 μg*l-1/mg p<0.001. Conclusions: Study suggested that Indian sub population closely mimics Caucasian population in terms of genotype expression for CYP3A5*3, who are expressing a non-functional enzyme for metabolism. Also, this study reinforces that population genotype CYP3A5*1 is significantly associated with lower C0/D ratio for Tac than the ones expressing homozygous CYP3A5*3 genotype. It also established the importance of pre-transplant genotyping, for better individualization of Tac doses. Further studies are suggested for population pharmacokinetic modelling study in future to derive starting dosage of Tac based on profiling of CYP3 genetics in recipients.